KONSEP KOTAK GEOWISATA DAN PENERAPANNYA DI DESTINASI PARIWISATA CEKUNGAN BANDUNG - Shandra Rama Panji Wulung (Journal of Tourism Destination and Attraction, 2021)
The Bandung Basin region as a tourism destination in West Java Province has a geodiversity that is used as a tourism resource. The process and forms of geodiversity supported by biodiversity and cultural diversity added value for geotourism development in Bandung Basin Tourism Destinations. On the other hand, developing tourism policy in the Bandung Basin still identifies geodiversity as a tourism attraction. This study discusses the method of valuing nature-based tourism attraction as a geotourism attraction in two tourism areas in Bandung Basin Tourism Destinations. The approach used is qualitative research with a unit of analysis based on geotourism box elements which include process element, form, tourism, geobasic, geohistory, and geo +. Primary data was obtained through field observations and semi-structured interviews at four tourism attractions in Pasir Pawon and Djuanda Forest Park Areas. While secondary data is obtained through desk study on previous research and local government policies related to tourism development. The study found that the assessment of four tourism attractions that have geological diversity is still identified as a natural tourist attraction. The geotourism box provides a reinterpretation of more diverse nature-based tourist attractions. Nature-based tourism attraction that meets the criteria based on geotourism box elements is classified as geotourism attraction.